2022
DOI: 10.3389/fimmu.2022.984323
|View full text |Cite
|
Sign up to set email alerts
|

Repeat controlled human malaria infection of healthy UK adults with blood-stage Plasmodium falciparum: Safety and parasite growth dynamics

Abstract: In endemic settings it is known that natural malaria immunity is gradually acquired following repeated exposures. Here we sought to assess whether similar acquisition of blood-stage malaria immunity would occur following repeated parasite exposure by controlled human malaria infection (CHMI). We report the findings of repeat homologous blood-stage Plasmodium falciparum (3D7 clone) CHMI studies VAC063C (ClinicalTrials.gov NCT03906474) and VAC063 (ClinicalTrials.gov NCT02927145). In total, 24 healthy, unvaccinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Last of all, we performed direct comparative analyses to ask whether the immune response to P. vivax differed from that to P. falciparum . Thirteen malaria-naive volunteers were infected with P. falciparum (clone 3D7) by direct blood challenge during the VAC063 ( 42 ) and VAC063C ( 43 ) CHMI trials; crucially, diagnosis and treatment thresholds were analogous to VAC069A ( P. vivax ) and circulating parasite densities were comparable at the peak of infection ( Figure 7A and Supplemental Figure 7 ). Moreover, the magnitude and kinetics of lymphopenia were equivalent between parasite species ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Last of all, we performed direct comparative analyses to ask whether the immune response to P. vivax differed from that to P. falciparum . Thirteen malaria-naive volunteers were infected with P. falciparum (clone 3D7) by direct blood challenge during the VAC063 ( 42 ) and VAC063C ( 43 ) CHMI trials; crucially, diagnosis and treatment thresholds were analogous to VAC069A ( P. vivax ) and circulating parasite densities were comparable at the peak of infection ( Figure 7A and Supplemental Figure 7 ). Moreover, the magnitude and kinetics of lymphopenia were equivalent between parasite species ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…To compare the immune response induced by P. vivax versus P. falciparum , we used data from 2 previously conducted CHMI trials (VAC063 and VAC063C); the VAC063 trial is described in full in Minassian et al ( 42 ) and the VAC063C trial is reported in Salkeld et al ( 43 ). In brief, 13 malaria-naive adult volunteers (10 in VAC063 and 3 in VAC063C) were inoculated with P. falciparum (clone 3D7) by intravenous injection of infected red cells (452–857 parasites per volunteer).…”
Section: Methodsmentioning
confidence: 99%
“…Additional support for the role of pre-erythrocytic immunity in delaying the onset of patency is suggested by an alternate CHMI model that challenged participants with blood-stage parasites and did not observe a patency delay 45 , 46 . Conversely, at peak parasitemia on treatment day the cytokine profile for both studies is similar, including an increase in both IL-10 and IL-1RA levels that could reduce inflammation 45 .…”
Section: Discussionmentioning
confidence: 96%
“…Participants were treated earlier if signs and symptoms were observed in association with blood film positivity at any parasite density, and on day 21 post-inoculation regardless of outcome. While qPCR was used as the primary measurement of parasitaemia because it is much more sensitive than microscopy at low density ( Bejon et al, 2006 ), thick film blood smears were also performed as an additional precaution, and participants were treated if they became blood film positive at any density, an approach that accords with that used in other CHMI studies ( Sheehy et al, 2012 ; Murphy et al, 2012 ; Hodgson et al, 2014 ; Kamau et al, 2014 ; Hodgson et al, 2015 ; Seilie et al, 2019 ; Salkeld et al, 2022 ). Participants were recruited during 2016, 2017, and 2018 into three successive cohorts from three different malaria transmission zones: Kilifi North (no- to low-transmission) and Kilifi South (moderate transmission), both on the coast, and Ahero (moderate to high transmission) in Western Kenya.…”
Section: Methodsmentioning
confidence: 99%